Some soil-inhabiting mites (Acari: Mesostigmata) from Kazakhstan, with description of a new species of Gaeolaelaps Evans & Till (Acari: Laelapidae) - Joharchi, Omid; Issakova, Aigerim K.; Asyamova, Olga S.; Sarcheshmeh, Mohammadhassan Abbasi; Tolstikov, Andrei V. (Zootaxa, 2020)
This paper presents ten species of eight genera and four families (Ameroseiidae, Ascidae, Blattisociidae, Laelapidae) of soil-inhabiting mesostigmatic mites in Kazakhstan. Eight of them are species that are recorded for the first time in Kazakhstan: Ameroseius corbiculus (Sowerby, 1806), Antennoseius (Vitzthumia) oudemansi (Thor, 1930), Cosmolaelaps lutegiensis (Shcherbak, 1971), C. markewitschi (Pirianyk, 1959), Gaeolaelaps nolli (Karg, 1962), Laelaspis astronomicus (Koch, 1839), Lasioseius ometes (Oudemans, 1903), and Pseudoparasitus missouriensis (Ewing, 1909). In addition, Gaeolaelaps kanati Joharchi & Issakova sp. nov. is described from Kazakhstan, based on morphological characters of the adult female.